Porphyrin Photoabsorption and Fluorescence Variation with Adsorptive Loading on Gold Nanoparticles - Shinohara, Akira; Shao, Guang; Nakanishi, Takashi; Shinmori, Hideyuki (Frontiers in Chemistry, 2021)
Here we report the photophysical structure–property relationship of porphyrins adsorbed on gold nanoparticles. The number of porphyrin–alkanethiolate adsorbates per particle was adjusted by a post-synthetic thiol/thiolate exchange reaction on 1-dodecanethiolate-protected gold nanoparticles. Even with a low loading level of adsorbates (<10% of all thiolate sites on gold nanoparticles), the shoulder absorption at the Soret band was intensified, indicating the formation of aggregates of porphyrin adsorbates on the nanoparticles. Steady-state fluorescence quantum yields could be adjusted by the bulkiness of substituents at the meso-positions of the porphyrin or the methylene linker chain length, regardless of the porphyrin loading level and the nanoparticle diameter.